Antarctic subglacial trace metal mobility linked to climate change across termination III - G. Piccione; T. Blackburn; P. Northrup; S. Tulaczyk; T. Rasbury (The Cryosphere, 2025)
Antarctic meltwater is a significant source of iron that fertilizes present-day Southern Ocean ecosystems and may enhance marine carbon burial on geologic timescales. However, it remains uncertain how the nutrient flux from the subglacial system changes through time, particularly in response to climate, due to an absence of geologic records detailing element mobilization beneath ice sheets. In this study, we present a 25 kyr record of aqueous trace metal cycling in subglacial water beneath the David Glacier catchment measured in a subglacial chemical precipitate that formed across glacial termination III (TIII), from 259.5 to 225 ka. The deposition rate and texture of this sample describe a shift in subglacial meltwater flow following the termination. Alternating layers of opal and calcite deposited in the 10 kyr prior to TIII record centennial-scale subglacial flushing events, whereas reduced basal flushing resulted in slower deposition of a trace-metal-rich (Fe, Mn, Mo, Cu) calcite in the 15 kyr after TIII. This sharp increase in calcite metal concentrations following TIII indicates that restricted influx of oxygen from basal ice melt to precipitate-forming waters caused dissolution of redox-sensitive elements from the bedrock substrate. The link between metal concentrations and climate change in this single location across TIII suggests that ice motion may play an important role in subglacial metal mobilization and discharge, whereby heightened basal meltwater flow during terminations supplies oxygen to subglacial waters along the ice sheet periphery, reducing the solubility of redox-sensitive elements. As the climate cools, thinner ice and slower ice flow decrease subglacial meltwater production rates, limiting oxygen delivery and promoting more efficient mobilization of subglacial trace metals. Using a simple model to calculate the concentration of Fe in Antarctic basal water through time, we show that the rate of Antarctic iron discharge to the Southern Ocean is sensitive to this heightened mobility and may therefore increase significantly during cold climate periods.